Nature’s Moral Voice as Eco-Ethics: Reading Mary Oliver’s A Thousand Mornings - Ghimire, Kusum (Bon Voyage, 2025)
This paper explores the eco-ethical dimensions in Mary Oliver’s poetry collection A Thousand Mornings. It analyzes Oliver’s portrayal of nature as a moral and spiritual guide through close readings of selected poems. The research draws framework from environmental ethics, particularly eco-ethics. And, the study examines how Oliver challenges anthropocentric perspectives and advocates for a reverent, interconnected relationship between humans and the natural world. By weaving spiritual contemplation with vivid imagery and minimalist language, Oliver redefines the act of poetic observation as a form of ecological awareness and moral engagement. Her verse becomes a medium through which the reader is invited to reflect on their ethical responsibility toward the environment, proposing that attention, gratitude, and humility are essential virtues in this relationship. The analysis positions Oliver as a Neo-Transcendentalist, whose work continues the lineage of Emersonian thought which contributes in the discourse on eco-poetry and environmental ethics.